AB0939 POLYMYALGIA RHEUMATICA FOLLOWING INFECTIVE TRIGGERS OR VACCINATIONS: A DIFFERENT SUBSET OF DISEASE?. (13th June 2020) - Conticini, E.; Falsetti, P.; Acciai, C.; Baldi, C.; Bardelli, M.; Gentileschi, S.; Cantarini, L.; Frediani, B.
Abstract : Background: Polymyalgia rheumatica (PMR) is the most common inflammatory disorder of elderly; an association with environmental triggers and deregulated immune response has been described. Objectives: The aim of this study was to investigate the presence of environmental triggers before the onset of PMR and its association to a particular subset of disease. Methods: The database of 58 consecutive PMR patients recruited from a single rheumatology secondary care setting was retrospectively analyzed to investigate the frequency of environmental triggers and correlations with clinical characteristics. Patients underwent multidistrict ultrasound examination of both proximal and distal sites. Laboratory tests were repeated after one month from first visit, when steroids were started, and about every three months during follow-up (for at least 24 months) Results: Fifteen PMR patients (26%) described a connection with environmental agents: six PMR patients reported a vaccination, 3 an upper respiratory tract infection and 1 pneumonia before the onset of disease. Five patients reported seasonal influenza as trigger of PMR. The model of multivariate linear regression which better predicted a shorter time to normalize inflammatory reactants (R squared 27, 46%, p=0, 0042) comprised the presence of an environmental trigger and a higher CRP. A linear regression analysis confirmed an inverse correlation between CRP at onset ant time to normalize inflammatory reactant (r= -0, 3031, p=0, 0208). A significant correlation was demonstrated between presence of environmental trigger and shorter time to normalize inflammation (r=-0, 5215, p<0, 0001), lesser frequency of gleno-humeral synovitis on US (r=-0, 3774, p=0, 0038). Conclusion: Our work describes a correlation between environmental triggers in PMR and higher CRP at diagnosis and faster response to therapy. We may suppose that these patients belong to a more specific subtype of PMR, in whom external stimuli, such as vaccinations or infections, may lead to a deregulated response within the context of an impaired immune and endocrine system. We recommend a systematic research of previous infections or vaccination in recent onset PMR Disclosure of Interests: None declared